2017
DOI: 10.1186/s40594-017-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an afterschool STEM program on students’ motivation and engagement

Abstract: Background: One significant factor in facilitating students' career intentions and persistence in STEM (science, technology, engineering, and mathematics) fields is targeting their interests and motivation before eighth grade. To reach students at this critical stage, a design-based afterschool STEM program, titled Studio STEM, was implemented to foster motivation and engagement in STEM topics and activities. The purpose of this study is twofold: (a) to investigate how Studio STEM affected students' beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 54 publications
2
93
0
1
Order By: Relevance
“…For instance, in an extensive literature review of peer-reviewed articles describing interest, motivation, and attitudes toward science and technology, found that only 14 out of a total of 189 survey-based studies published between 2000 and 2012 specifically examined OST STEM opportunities (including summer camps, competitions, science fairs, and field trips). However, a growing body of literature indicates that participation in STEM-focused afterschool programs increases self-reported STEM interest, engagement, motivation, persistence, and identity (Chittum, Jones, Akalin, & Schram, 2017;Dabney et al, 2012;Young, Ortiz, & Young, 2017).…”
Section: Review Of Research On Stem Attitudes In Afterschool Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in an extensive literature review of peer-reviewed articles describing interest, motivation, and attitudes toward science and technology, found that only 14 out of a total of 189 survey-based studies published between 2000 and 2012 specifically examined OST STEM opportunities (including summer camps, competitions, science fairs, and field trips). However, a growing body of literature indicates that participation in STEM-focused afterschool programs increases self-reported STEM interest, engagement, motivation, persistence, and identity (Chittum, Jones, Akalin, & Schram, 2017;Dabney et al, 2012;Young, Ortiz, & Young, 2017).…”
Section: Review Of Research On Stem Attitudes In Afterschool Settingsmentioning
confidence: 99%
“…Importantly, STEM interest is malleable and can be positively changed by afterschool programs. For instance, Chittum et al (2017) found that fifth to seventh graders participating in a design-based STEM program (90 min per week for six to 12 weeks) that uses an inquiry-based approach reported significantly higher levels of science interest and competence than peers who did not participate.…”
Section: Review Of Research On Stem Attitudes In Afterschool Settingsmentioning
confidence: 99%
“…Wang (2012) stated that the purpose of the STEM integration courses was to improve problemsolving skills. However, when the literature is examined, it is seen that STEM seminars also have positive effects on the attitude, interest, academic success, scientific process skills and motivation of the individuals (Chittum, Jones, Akalin & Schram, 2017;Olivarez, 2012;Park & Yoo, 2013).These results show that STEM seminars have a positive effect also on different variables.…”
Section: Discussionmentioning
confidence: 98%
“…Many students have concluded that the STEM subjects are too challenging, yet boring and uninteresting, which limits their participation in STEM subjects and activities (Roberts et al, 2018). Chittum, Jones, Akalin, and Schram (2017) have identified interest and motivation as important components in inspiring students to pursue their study in STEM because it contributes to students' learning and success in retaining STEM content. Based on the findings of this study, the students expressed that the partnership changed their perception about science.…”
Section: Discussionmentioning
confidence: 99%